Pengaruh Ekstrak Alpinia galanga L Terhadap Produksi Biofilm pada Escherichia coli - Wahyudi, Didik; Wael, Syahran (Jurnal Farmasi (Journal of Pharmacy), 2021)
Escherichia coli is a Gram-negative rod-shaped bacteria, capable of causing infection in several parts of the body, and has been found to be resistant to various antibiotics, one of the contributing factors is its ability to form biofilms in tissues. Alpinia gallanga L has the ability to inhibit biofilm formation against several bacteria. The purpose of this study was to determine the ability of Alpinia galangl L extract in inhibiting the production of Escherichia coli biofilm. This research began with the extraction of galangal rhizome with ethanol using the masersion method, then made the concentrations of 10%, 20%, 30%, 40%, and 50%. Escherichia coli was isolated from cases of Urinary Tract Infection (UTI). then do the physiological characterization and sensitivity test to antibiotics. Inhibition test for Escherichia coli biofilm was carried out using the microtiter plate culture method using a spectrophotometer at a wavelength of 595nm. The measurement results of biofilm production were 0.1% Optical Density crystal violet value, each treatment used 8 replications, the data obtained were analyzed by One Way Anova. . The results showed that the extract of Alpinia galanga L was able to inhibit the production of Escherichia coli biofilm at a concentration of 30%.